Correction to: electronic cigarette use behaviors and motivations among smokers and non-smokers - Thomas E. Sussan; Fatima G. Shahzad; Eefa Tabassum; Joanna E. Cohen; Robert A. Wise; Michael J. Blaha; Janet T. Holbrook; Shyam Biswal (BMC, 2018)
Abstract After publication of the article [1], it has been brought to our attention that there is a funding acknowledgement missing. The authors would also like to include "Dr. Michael Joseph Blaha is funded by the American Heart Association Tobacco Regulatory Center, funding number: 1P50HL120163".